Implications of Globalized Human Resource Management Practices in Organizations in Pakistan - An Academic Perspective - Hyder, Mustafa; Faisal, Tehmina (European Scientific Journal, ESJ, 2019)
Since the 1940’s, businesses have moved beyond local markets and gradually developed into one sophisticated multiethnic and multiracial economies; a trend we today conceptualize as globalization. Through liberated flow of technology and human resources across local boundaries, international organizations are enabled to explore infinite opportunities within limited resources. Globalization, however, has immensely increased responsibilities of the HR practitioners specifically in terms of employee growth and wellbeing. Comprehensive data collection technique of structured open ended interviews from HR practitioners of multi-national and local business concerns was utilized, simultaneously relevant literature was also reviewed to further conceptualize and clarify the implications of implementing globalized HR practices to organizations performing in local scenario. This analytical paper explores HR practices in Pakistan and how efficacious organizations embrace globalization as a challenging yet profitable phenomenon.